2013
DOI: 10.1021/jp408530w
|View full text |Cite
|
Sign up to set email alerts
|

Isosteric and Nonisosteric Base Pairs in RNA Motifs: Molecular Dynamics and Bioinformatics Study of the Sarcin–Ricin Internal Loop

Abstract: The Sarcin-Ricin RNA motif (SR motif) is one of the most prominent recurrent RNA building blocks that occurs in many different RNA contexts and folds autonomously, i.e., in a context-independent manner. In this study, we combined bioinformatics analysis with explicit-solvent molecular dynamics (MD) simulations to better understand the relation between the RNA sequence and the evolutionary patterns of SR motif. SHAPE probing experiment was also performed to confirm fidelity of MD simulations. We identified 57 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 85 publications
(234 reference statements)
0
51
0
Order By: Relevance
“…Further, similar to experiments, different simulation tasks have different accuracy requirements. For example, when investigating structural dynamics of sarcin‐ricin loop (SRL), we wish to satisfy all its signature interactions . When complementing sequence alignments on substitutions in the SRL, we aim to achieve a qualitative ranking of the diverse substitutions which surpasses rankings by bioinformatics tools .…”
Section: Unbiased Versus Enhanced‐sampling Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, similar to experiments, different simulation tasks have different accuracy requirements. For example, when investigating structural dynamics of sarcin‐ricin loop (SRL), we wish to satisfy all its signature interactions . When complementing sequence alignments on substitutions in the SRL, we aim to achieve a qualitative ranking of the diverse substitutions which surpasses rankings by bioinformatics tools .…”
Section: Unbiased Versus Enhanced‐sampling Simulationsmentioning
confidence: 99%
“…For example, when investigating structural dynamics of sarcin‐ricin loop (SRL), we wish to satisfy all its signature interactions . When complementing sequence alignments on substitutions in the SRL, we aim to achieve a qualitative ranking of the diverse substitutions which surpasses rankings by bioinformatics tools . In contrast, when simulating the whole ribosome, we do not expect structural details on a level of single non‐Watson‐Crick base pairs …”
Section: Unbiased Versus Enhanced‐sampling Simulationsmentioning
confidence: 99%
“…S-turn motifs in other RNAs often participate in binding of proteins and RNA (12,(23)(24)(25) and are important for ribosome assembly, translation, and viral replication and packaging (12,19,(26)(27)(28). S-turn formation depends not only on base-base interactions but also on base-phosphate backbone interactions (29). The G37U and A57C single mutations reduced cross-linking, as predicted, but the G37U, A57C double substitution, which was predicted to introduce an isosteric pair at the 37-57 position, did not restore cross-linking efficiency (Fig.…”
mentioning
confidence: 99%
“…For example, a recent study on Sarcin-Ricin internal loop motif (SR-motif) reports two structurally observed variants of the reference native SR-motif (variant 0), characterized by isosteric substitutions of two different A:G H:S Trans base pairs, respectively. Variant 1 involves substitution of the A18:G4 H:S Trans base pair by C18:C4 H:S Trans, and variant 6 involves substitution of the A8:G15 H:S Trans base pair by A8:A15 H:S Trans ( 53 ) (see Supporting information S1 for details). In course of MD simulation, the C18:C4 base pair, in the flexible region of variant 1, showed far greater geometric fluctuations compared with the corresponding A18:G4 base pair in the variant 0.…”
Section: Resultsmentioning
confidence: 99%